The Influence of Behavioral Factors on Fatigue Presentation in College Students - Goltermann, Danielle (East Carolina University, 2017)
On average, college students report that they experience more sleep difficulties in comparison to healthy adults which is related to impairments in memory, learning, and the ability to concentrate and problem solve (Buboltz, Brown, & Soper, 2001; National Institutes of Health, 2012). The impact of poor sleep patterns on daily functioning may be due to increased fatigue during the day. Fatigue, a nationally recognized health concern among adults3 has not been fully examined in college students (Schiffert Health Center, 2010). Also, there is limited research on factors that may impact fatigue presentation or mediate the relationship between poor sleep and fatigue. This information is essential for designing effective intervention programs. Other behavioral factors that may influence fatigue include college students’ poor eating habits, participation in drinking activities, and physical activity patterns. Research in chronically ill populations have linked sleep disturbance and these behavioral factors to fatigue presentation (Strober & Arnett, 2005; Gerber, Stout, McGarvey, Soballe, Shieh, Diao, Pfalzer, 2011). However, the relations between these factors and fatigue have not been examined in healthy college students. This study described fatigue in a sample of college students and examined the relative contributions of sleep, diet, physical activity level, and alcohol consumption on fatigue presentation in college students. Participants included 191 undergraduate college students ranging in age from 18 to 38 years old. The majority of participants reported experiencing fatigue in the past month. Poor sleep quality, and high levels of uncontrolled eating and emotional eating were related to fatigue presentation, however, sleep quality was the only behavioral factor that significantly and uniquely predicted fatigue. Additional research should collect data from a broader age range of undergraduate students and should utilize an electronic diary to collect data. Clinical implications include the identified need to focus on sleep when developing health and wellness programs that target fatigue.
Keywords: fatigue; college students; sleep; diet; physical activity; alcohol use